Emerging roles of Hippo signaling in inflammation and YAP-driven tumor immunity. (10th July 2018) - Zhou, Yuhang; Huang, Tingting; Zhang, Jinglin; Cheng, Alfred S.L.; Yu, Jun; Kang, Wei; To, Ka Fai
Abstract: Initially identified as a cell and organ size controller, Hippo pathway turns into a hotspot for researchers. Within recent years, more and more mechanisms about Hippo pathway were uncovered. Even though Hippo signaling has been revealed to exert controversial roles according to different cell context and microenvironment, which is because of its diversified interplays with a great variety of signaling transduction cascades; mechanisms other than size-limitation, however, remain to be elucidated. Recently, a growing number of studies tend to put Hippo on inflammatory and immunological focus: its antimicrobial role in flies, its pro- or anti-inflammation in mammals, as well as its relevance to cancerous immunity. From inflammation to tumor immunogenicity, Hippo has been gradually justified to play a crucial role. This review summarized the latest findings regarding the involvement of Hippo pathway in immunity, and a more comprehensive understanding of Hippo pathway will shed light on clinical translational potential even precision medicine. Highlights: This review highlighted the anti-inflammatory role of Hippo-YAP cascades and its involvement with cancer immunity. This review summarized the non-proliferative function of Hippo-YAP axis in both drosophila and mammalian cells. This review comprehensively discussed about the clinical translational potential of Hippo-YAP signal regarding immunotherapy.